Indonesian Education Services Quality: The Influence of Leadership and Total Quality Management - Fauzi, Anis; Suryapermana, Nana; Wahyuni, Ayu; Gofur, Ridwan (Pedagogika, 2023)
The study aimed to understand the influence of leadership and Total Quality Management (TQM) implementation on the educational services quality in Banten, Indonesia. Research data is obtained through surveys, observation sheets, and documentation studies. The findings showed that leadership and TQM implementation positively affect the educational services quality by 11.8% and 19%. Two variables are also combined as independent variables that positively impact the educational services quality.